Prime-Boost Vaccination With a Novel Hemagglutinin Protein Produced in Bacteria Induces Neutralizing Antibody Responses Against H5-Subtype Influenza Viruses in Commercial Chickens - Sączyńska, Violetta; Romanik-Chruścielewska, Agnieszka; Florys, Katarzyna; Cecuda-Adamczewska, Violetta; Łukasiewicz, Natalia; Sokołowska, Iwona; Kęsik-Brodacka, Małgorzata; Płucienniczak, Grażyna (Frontiers in Immunology, 2019)
The highly pathogenic (HP) avian influenza virus (AIV), H5N1 and reassortant H5-subtype HPAIVs, H5N2, H5N6, and H5N8, cause high mortality in domestic birds, resulting in economic losses in the poultry industry. H5N1 and H5N6 also pose significant public health risks and H5N1 viruses are a permanent pandemic threat. To control HPAIVs, eukaryotic expression systems have traditionally been exploited to produce vaccines based on hemagglutinin (HA), a protective viral antigen. In contrast, we used a bacterial expression system to produce vaccine targeting the HA protein. A fragment of the HA ectodomain from H5N1, with a multibasic cleavage site deletion, was expressed in Escherichia coli, refolded, and chromatographically purified from inclusion bodies. The resulting antigen, rH5-E. coli, was validated in terms of conformational integrity and oligomerization status. Previously, the protective efficacy of rH5-E. coli adjuvanted with aluminum hydroxide, has been positively verified by challenging the specific pathogen-free layer chickens with homologous and heterologous H5N1 HPAIVs. Protection was provided primarily by the H5 subtype-specific antibodies, as detected in the FluAC H5 test. The present studies were conducted to assess the performance of alum-adjuvanted rH5-E. coli in commercial birds. Broiler chickens were vaccinated twice with 25 µg of rH5-E. coli at 2- and 4-week intervals, while the layer chickens were vaccinated with 5- to 25-µg antigen doses at 4- and 6-week intervals. Post-vaccination sera were analyzed for anti-H5 HA antibodies, using homologous ELISA and heterologous FluAC H5 and hemagglutination inhibition (HI) tests. Prime-boost immunizations with rH5-E. coli elicited H5 HA-specific antibodies in all the chickens tested. Two antigen doses administered at 4- or 6-week intervals were sufficient to induce neutralizing antibodies against H5-subtype HAs; however, they were ineffective when applied with a 2-week delay. In the layers, 80% to 100% of individuals developed antibodies that were active in the FluAC H5 and/or HI tests. A dose-sparing effect was seen when using the longer prime-boost interval. In the broiler chickens, 62.5% positivity was achieved in the FluAC H5 and/or HI tests. The trials confirmed the vaccine potential of rH5-E. coli and provided indications for anti-influenza vaccination with respect to the chicken type and immunization scheme.